2021
DOI: 10.1186/s43556-021-00027-2
|View full text |Cite
|
Sign up to set email alerts
|

GMPPB-congenital disorders of glycosylation associate with decreased enzymatic activity of GMPPB

Abstract: The congenital disorders of glycosylation (CDG) are a family of metabolic diseases in which glycosylation of proteins or lipids is deficient. GDP-mannose pyrophosphorylase B (GMPPB) mutations lead to CDG, characterized by neurological and muscular defects. However, the genotype-phenotype correlation remains elusive, limiting our understanding of the underlying mechanism and development of therapeutic strategy. Here, we report a case of an individual presenting congenital muscular dystrophy with cerebellar invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…In our report, the two patients with this homozygous variant presented with an earlier onset of muscle weakness and showed moderate improvement in muscle weakness on anticholinesterase inhibitors unlike the report above. This supports the previous reports that noted that there is no clear genotypephenotype correlation in patients with GMPPB-MDDG (Liu et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…In our report, the two patients with this homozygous variant presented with an earlier onset of muscle weakness and showed moderate improvement in muscle weakness on anticholinesterase inhibitors unlike the report above. This supports the previous reports that noted that there is no clear genotypephenotype correlation in patients with GMPPB-MDDG (Liu et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Disease associated GMPPB variants include missense, nonsense and frameshift mutations ( Astrea et al, 2018 ; Tian et al, 2019 ) and are considered to result in GMPPB loss-of-function. Functional studies reported decreased enzymatic activities of approximately up to 90% ( Liu et al, 2021 ). Here, we show that the total loss of GMPPB activity by disrupting the catalytic nucleotide transferase domain results in embryonic lethality in mice suggesting a pivotal role of GMPPB activity for early development.…”
Section: Discussionmentioning
confidence: 99%
“…GMPPB is crucial for the conversion of mannose-1-phosphate and guanosine triphosphate into GDP-mannose, which is required as a mannose donor for glycosylation ( Ning and Elbein, 2000 ). Bi-allelic mutations in GMPPB are associated with variable disorders such as muscular dystrophy and other neurological symptoms including intellectual disability ( Carss et al, 2013 ; Belaya et al, 2015 ; Liu et al, 2021 ). Additional symptoms such as cerebellar hypoplasia, seizures, or cardiac involvement are reported for some patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that reduced GMPPB abundance leads to decreased GDP-mannose levels and thus affects neuronal and muscle development ( 4 , 31 , 32 ). For example, motor neurons were shortened ( 4 ), and an early marker of pan-neuronal cells was remarkably decreased in GMPPB knockdown zebrafish ( 33 ).…”
Section: Discussionmentioning
confidence: 99%